Phenotypes of Severe Cutaneous Adverse Reactions Caused by Nonsteroidal Anti-inflammatory Drugs - Lee, Suh-Young (Allergy Asthma Immunol Res, 2018)
PURPOSE: Nonsteroidal anti-inflammatory drugs (NSAIDs) are common cause of severe cutaneous adverse reactions (SCARs). The present study aimed to investigate the characteristics of SCARs induced by NSAIDs in the Korean SCAR registry. METHODS: A retrospective survey of NSAID-induced SCARs recorded between 2010 and 2015 at 27 university hospitals in Korea was conducted. Clinical phenotypes of SCARs were classified into Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), SJS-TEN overlap syndrome and drug reaction with eosinophilia and systemic symptoms (DRESS). Causative NSAIDs were classified into 7 groups according to their chemical properties: acetaminophen, and propionic, acetic, salicylic, fenamic and enolic acids. RESULTS: A total of 170 SCARs, consisting of 85 SJS, 32 TEN, 17 SJS-TEN overlap syndrome and 36 DRESS reactions, were induced by NSAIDs: propionic acids (n=68), acetaminophen (n=38), acetic acids (n=23), salicylic acids (n=16), coxibs (n=8), fenamic acids (n=7), enolic acids (n=5) and unclassified (n=5). Acetic acids (22%) and coxibs (14%) accounted for higher portions of DRESS than other SCARs. The phenotypes of SCARs induced by both propionic and salicylic acids were similar (SJS, TEN and DRESS, in order). Acetaminophen was primarily associated with SJS (27%) and was less involved in TEN (10%). DRESS occurred more readily among subjects experiencing coxib-induced SCARs than other NSAID-induced SCARs (62.5% vs. 19.7%, P = 0.013). The mean time to symptom onset was longer in DRESS than in SJS or TEN (19.1 ± 4.1 vs. 6.8 ±1.5 vs. 12.1 ± 3.8 days). SCARs caused by propionic salicylic acids showed longer latency, whereas acetaminophen- and acetic acid-induced SCARs appeared within shorter intervals. CONCLUSIONS: The present study indicates that the phenotypes of SCARs may differ according to the chemical classifications of NSAIDs. To establish the mechanisms and incidences of NSAID-induced SCARs, further prospective studies are needed.